A fast and high-efficiency electrochemical exfoliation strategy towards antimonene/carbon composites for selective lubrication and sodium–ion storage applications. Issue 8 (9th February 2022) - Zhang, Renhui; Yang, Yingchang; Guo, Lei; Luo, Yuzhou
Abstract : Antimonene/carbon fabricated through electrochemical exfoliation in a Na2 SO4 and ethylene glycol mixed solution exhibits selective lubrication and extraordinary sodium–ion storage performance. Abstract : Two-dimensional (2D) layered antimony (Sb) materials are of importance due to their unique physicochemical properties, and they can be easily electrochemically exfoliated from bulk Sb in Na2 SO4 electrolyte solution. However, the exfoliation yield is quite low and the exfoliated products are easily oxidized to Sb2 O3, which prohibits their practical engineering applications. Herein, an antimonene/carbon composite is successfully fabricated with a high exfoliation yield through electrochemical exfoliation of bulk antimony chunk in a mixed electrolyte solution consisting of Na2 SO4 and ethylene glycol. When the as-fabricated antimonene/carbon composite is added into PAO6 oil, the lubrication system exhibits a selective lubrication performance when sliding against GCr15 and YG8 ball, and the antiwear enhancement can be further improved by sliding against a YG8 ball. Besides, the antimonene/carbon composite can provide reliability and enough ion corridors during the charge/discharge processes. When tested as an anodic material for sodium–ion batteries, it exhibits a large capacity of 485.0 mA h g −1 at a current density of 200 mA g −1 after 150 cycles and a remarkable rate capability (334.5 mA h g −1 at 5 A g −1 ).